Insulin Resistance Remission Following Laparoscopic Roux-en-Y Gastric Bypass and Laparoscopic Sleeve Gastrectomy in Chinese Type 2 Diabetes Mellitus Patients With a Body Mass Index of 27.5–32.5 kg/m2 - Luo, Ping; Cao, Yaoquan; Li, Pengzhou; Wang, Guohui; Song, Zhi; Li, Weizheng; Su, Zhihong; Zhou, Hui; Yi, Xianhao; Fu, Zhibing; Sun, Xulong; Tang, Haibo; et al. (Frontiers in Physiology, 2021)
Background: Insulin resistance (IR) is closely associated with the pathogenesis of type 2 diabetes mellitus (T2DM). However, remission of insulin sensitivity after bariatric surgery in patients with T2DM and a body mass index (BMI) of 27.5–32.5 kg/m2 has not been fully elucidated. Methods: Thirty-six T2DM patients with a BMI of 27.5–32.5 kg/m2 were prospectively consecutively recruited for laparoscopic Roux-en-Y gastric bypass (LRYGB) or laparoscopic sleeve gastrectomy (LSG). Hyperinsulinemic euglycemic clamp, oral glucose tolerance test (OGTT), and other indicators were tested at baseline and 6 months postoperative. Glucose disposal rate (GDR), time to reach euglycemia, homeostatic model assessment of IR, quantitative insulin sensitivity check index (QUICKI), triglyceride glucose (TyG) index, 30-min insulinogenic index (IGI30), and disposition index (DI) were calculated at baseline and 6 months after surgery. The criterion for remission in T2DM patients was the achievement of the triple composite endpoint. Results: Anthropometric and glucolipid metabolism parameters significantly improved following surgery. The GDR increased significantly from baseline to 6 months after LRYGB (from 4.28 ± 1.70 mg/kg/min to 8.47 ± 1.89 mg/kg/min, p < 0.0001) and LSG (from 3.18 ± 1.36 mg/kg/min to 7.09 ± 1.69 mg/kg/min, p < 0.001). The TyG index decreased after surgery (RYGB group, from 9.93 ± 1.03 to 8.60 ± 0.43, p < 0.0001; LSG group, from 10.04 ± 0.79 to 8.72 ± 0.65, p = 0.0002). There was a significant reduction in the IGI30 (RYGB group, from 2.04 ± 2.12 to 0.83 ± 0.47, p = 0.005; LSG group, from 2.12 ± 1.73 to 0.92 ± 0.66, p = 0.001). The mean DI significantly increased from 1.14 ± 1.35 to 7.11 ± 4.93 in the RYGB group (p = 0.0001) and from 1.25 ± 1.78 to 5.60 ± 4.58 in the LSG group (p = 0.003). Compared with baseline, HOMR-IR, QUICKI, area under the curve-C-peptide release test (AUC-CRT), and AUC-OGTT were significantly changed at 6 months postoperative. Overall, 52.63% of patients in the LRYGB group versus 29.41% of patients in the LSG group achieved the triple composite endpoint. Conclusion: Both LRYGB and LSG effectively induced remission of IR in patients with T2DM and a BMI of 27.5–32.5 kg/m2.